The 1st Baltic Osseointegration Academy and Lithuanian University of Health Sciences Consensus Conference 2016. Summary and Consensus Statements: Group I - Peri-Implantitis Aetiology, Risk Factors and Pathogenesis - Claudio Stacchi; Mindaugas Pranskunas; Lukas Poskevicius; Gintaras Juodzbalys; Ricardas Kubilius; Ryo Jimbo; Federico Berton; Giuseppe Perinetti; Andrea Frassetto; Teresa Lombardi; Aiman Khoury; Francesca Andolsek; et al. (Stilus Optimus, 2016)
Introduction: The task of Group 1 was to review and update the existing data concerning aetiology, risk factors and pathogenesis of peri-implantitis. Previous history of periodontitis, poor oral hygiene, smoking and presence of general diseases have been considered among the aetiological risk factors for the onset of peri-implant pathologies, while late dental implant failures are commonly associated with peri-implantitis and/or with the application of incorrect biomechanical forces. Special interest was paid to the bone cells dynamics as part of the pathogenesis of peri-implantitis. Material and Methods: The main areas indagated by this group were as follows: influence of smoking, history of periodontitis and general diseases on peri-implantitis development, bio-mechanics of implant loading and its influence on peri-implant bone and cellular dynamics related to the pathogenesis of peri-implantitis. The systematic reviews and/or meta-analyses were registered in PROSPERO, an international prospective register of systematic reviews: http://www.crd.york.ac.uk/PROSPERO/. The literature in the corresponding areas of interest was screened and reported following the PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis) Statement: http://www.prisma-statement.org/. Method of preparation of the systematic reviews, based on comprehensive search strategies, was discussed and standardized. The summary of the materials and methods employed by the authors in preparing the systematic reviews and/or meta-analyses is presented in Preface chapter. Results: The results and conclusions of the review process are presented in the respective papers. One systematic review with meta-analysis, three systematic reviews and one theoretical analysis were performed. The group's general commentaries, consensus statements, clinical recommendations and implications for research are presented in this article.